Analysis of the Intensity of Access to Pornography on Social Media and Teenagers' Social Interactions with Peers - Aughea Rosita Putri (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2024)
The adolescent is someone aged 10-18 years. Adolescents have characteristics, and one of the characteristics that arises in adolescents is the emergence of fantasies about sexual activity (pornography) so at this time adolescents begin to access pornography, previous research stated that as many as 82.2% of adolescents are often exposed to pornography via electronics. Adolescents who have reached addiction to pornography will have one of the signs, namely difficulties in social interaction. To determine the relationship between the intensity of access to pornography on social media and the social interaction of adolescents with peers at SMA Z Jakarta in 2023. Methods: Research with a quantitative approach to the cross-sectional design. The research sample is Z Jakarta High School students for the 2022/2023 academic year as many as 98 teenagers. The sampling technique is simple random sampling. Retrieval of individual characteristic questionnaire data (personality type questionnaire, interaction questionnaire with parents), pornography access intensity questionnaire, and social interaction of adolescents with peers that are valid and reliable. Data analysis using chi-squares test. Results: The results showed that 75.5% of respondents had low-intensity access to pornography on social media, and 54.1% of respondents had high interaction with peers. Data analysis using the chi-square test found that there was a relationship between the two variables with ρ-Value = 0.010. The level of access to pornography will affect the good or bad of someone's interaction. Conclusion: The results of the study suggest that adolescents can demonstrate wise behavior in using social media in order to avoid negative behavior, and to be able to increase positive behavior in socializing or interacting with peers.